An energetic criterion for the development of life in an exoplanet - Velten, Hermano; Delladea, Douglas; Primola, Arthur (Cadernos de Astronomia, 2022)
I this article we review the Proportional Evolutionary Time hypothesis recently proposed in the literature. This proposal suggests a relation between the maximum incident energy on the surface of a exoplanet and the time required for the evolution of complex life. As a consequence, one can also suggest a relation to the spectral classification of the host star and the probability that one its exoplanets has attended the energetic conditions for the development of life. We also discuss possible extensions and applications. As an instance of one of our results, we find that the incidence of energy on Venus is sufficient to allow the evolution of complex life. The same did not happen to Mars. We also found an counter example of the PET hypothesis. The exoplanet GJ 887 b orbits a M-type star and but has received energy enough for the development of complex life.
Keywords: astrobiology; exoplane; development of life